MODEL IMPLEMENTASI PAJAK UNTUK MEMINIMALKAN PENGHEMATAN PAJAK BADAN DI SALAH SATU KLINIK KAB. KEDIRI - Wulandari, Aprilya; Winarko, Sigit Puji; Kurniawan, Andy (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The higher income affects the high taxes that must be paid, so this reason is the factor that causes the research to be carried out. The high tax payable depends on the nominal income and profit of the company. One of the strategies that entrepreneurs do is to implement tax management or tax planning. Therefore, the procedure that can be done to minimize the payment of Pph 21 permanent employees is by making tax planning and implementing the gross up method. The research carried out aims to calculate tax payments in order to get the lowest possible nominal by implementing tax planning through Pph 21 permanent employees and in accordance with applicable laws and regulations. The research carried out implements descriptive quantitative analysis. From the results of the research conducted, it was found that tax planning by replacing the burden of Pph 21 allowances borne by business entities into tax allowances with the gross up method can minimize taxes with a nominal value of Rp. 27,026,874. So that the cash from the tax savings can be used for other purposes such as business entity development.